ANALISIS KESULITAN BELAJAR SISWA KELAS III SD DALAM MEMAHAMI KONSEP PERKALIAN DI SDN 010106 SEI SILAU BARAT - Anim, Anim; Ariyani, Dinda; Ningsih, Ruri Ayu; Emalia, Ruri (Smart Education, 2025)
Abstract: This research aims to analyze the difficulties experienced by third-grade students in understanding the concept of multiplication at SDN 010106 Sei Silau Barat. The study involved 19 students as research subjects and employed a descriptive qualitative method with data collected through written tests. The tests were designed to identify the types of difficulties students faced in learning the basic concept of multiplication, such as errors in memorizing multiplication facts, inability to associate multiplication with repeated addition, and mistakes in applying the concept to word problems. The findings revealed that most students still struggled to connect the concept of multiplication with the concrete meaning of repeated processes. This indicates that students have not yet developed a strong conceptual understanding of multiplication and tend to rely on rote memorization instead of meaningful comprehension. Furthermore, it was found that the main causes of these difficulties were insufficient conceptual understanding, learning habits focused on memorization, and the limited use of contextual learning media that could help visualize the concept. Therefore, it is suggested that teachers implement more concrete and contextual teaching approaches, such as using real-life examples, manipulatives, and visual aids, to help students grasp the meaning of multiplication deeply and meaningfully, fostering better understanding and long-term retention of mathematical concepts.Keyword: difficulties; students;multiplication;understanding;contextual.Abstrak: Penelitian ini bertujuan untuk menganalisis kesulitan yang dialami siswa kelas III dalam memahami konsep perkalian di SDN 010106 Sei Silau Barat. Subjek penelitian berjumlah 19 orang siswa. Metode penelitian yang digunakan adalah metode deskriptif kualitatif dengan teknik pengumpulan data melalui tes tertulis. Tes tersebut dirancang untuk mengidentifikasi jenis kesulitan yang dihadapi siswa dalam memahami konsep dasar perkalian, seperti kesalahan dalam menghafal fakta perkalian, ketidakmampuan mengaitkan perkalian dengan penjumlahan berulang, serta kesalahan dalam penerapan konsep pada soal cerita. Hasil penelitian menunjukkan bahwa sebagian besar siswa masih mengalami kesulitan dalam menghubungkan konsep perkalian dengan makna konkret dari proses berulang. Selain itu, ditemukan bahwa faktor utama penyebab kesulitan tersebut adalah kurangnya pemahaman konseptual, kebiasaan belajar yang mengandalkan hafalan, serta keterbatasan penggunaan media pembelajaran yang kontekstual. Berdasarkan hasil tersebut, disarankan agar guru menggunakan pendekatan pembelajaran yang lebih konkret dan kontekstual untuk membantu siswa memahami konsep perkalian secara mendalam. Temuan ini diharapkan dapat menjadi rujukan dalam pengembangan strategi pembelajaran matematika yang lebih efektif dan relevan dengan kebutuhan siswa sekolah dasar.Kata Kunci: kesulitan; perkalian; siswa; pemahaman; kontekstual.